Challenges of non-clinical safety testing for biologics: A Report of the 9th BioSafe European Annual General Membership Meeting. Issue 1 (1st January 2021) - Kissner, Thomas; Blaich, Guenter; Baumann, Andreas; Kronenberg, Sven; Hey, Adam; Kiessling, Andrea; Schmitt, Petra M.; Driessen, Wouter; Carrez, Chantal; Kramer, Daniel; Fretland, Jennifer; Richter, Wolfgang F.; et al.
ABSTRACT: New challenges and other topics in non-clinical safety testing of biotherapeutics were presented and discussed at the nineth European BioSafe Annual General Membership meeting in November 2019. The session topics were selected by European BioSafe organization committee members based on recent company achievements, agency interactions and new data obtained in the non-clinical safety testing of biotherapeutics, for which data sharing would be of interest and considered as valuable information. The presented session topics ranged from strategies of in vitro testing, immunogenicity prediction, bioimaging, and developmental and reproductive toxicology (DART) assessments to first-in-human (FIH) dose prediction and bioanalytical challenges, reflecting the entire space of different areas of expertise and different molecular modalities. During the 9 th meeting of the European BioSafe members, the following topics were presented and discussed in 6 main sessions (with 3 or 4 presentations per session) and in three small group breakout sessions: 1) DART assessment with biotherapeutics: what did we learn and where to go?; 2) Non-animal testing strategies; 3) Seeing is believing: new frontiers in imaging; 4) Predicting immunogenicity during early drug development: hope or despair?; 5) Challenges in FIH dose projections; and 6) Non-canonical biologics formats: challenges in bioanalytics, PKPD and biotransformation for complex biologics formats. Small group breakout sessions were organized for team discussion about 3 specific topics: 1) Testing of cellular immune function in vitro and in vivo ; 2) MABEL approach (toxicology and pharmacokinetic perspective); and 3) mRNA treatments. This workshop report presents the sessions and discussions at the meeting.